Análisis, diseño e implementación de un módulo web para la búsqueda y ubicación geográfica de empresas integrado al proyecto GeoBuy del Centro de Investigación, Desarrollo e Innovación Tecnológica (CIDITEC) usando las tecnologías Open Street Map y Google Maps. - Niebla Asanza, Erik Paúl (2013)
Nowadays, thanks to the advance of technology, e-commerce has become an important tool that allows businisses to offer products and services of permanent way, easy, and accessible from anywhere: due to the costs associated with creating and maintaing its own web site, many companies still do not have an online store, for this reason it has developed and implement the web application "GeoBuy"